Os intelectuais públicos negros e o processo de democratização da política brasileira (1985-2012) - Weber, Patrícia Amorim (Universidade Federal de São Carlos, 2022)
This research aims to analyze the role of black public intellectuals in the process of democratization in Brazil. In more specific terms, we will seek to respond to the following objectives: a) map and analyze the main political positions of black brazilian intellectuals in the debates on three political moments: National Constituent Assembly; law 10,639/2003 and affirmative actions for higher education; b) based on these positions, analyze what were the meanings of democracy conferred by them; c) analyze the meaning and consequences of the institutionalization of the racial relations agenda for the country's democratization process; d) analyze the public role of these intellectuals in the light of contemporary conceptions of black intellectuality. In methodological terms, we used Content Analysis to interpret the data collected through bibliographic research and semi-structured interviews. In addition, we rely on theoretical contributions from Cultural and Post-Colonial Studies. Briefly, the profile of the black public intellectual can be defined as one who argues that there is an intrinsic relationship between theory and politics. From this assumption, they engage politically in public spaces with the aim of fighting for the full insertion of black people in the democratic system, guaranteeing their basic rights as citizens. We could notice that the contribution of these intellectuals to the Brazilian democratization process took place, in general, in two aspects: 1) the first concerns political intervention in public spaces, by participating in and organizing demonstrations and/or being part of government positions; or even by occupying universities, creating research groups and strengthening public policies of racial equality within these spaces; 2) the second concerns the construction of an awareness of the role of blacks in Brazilian social formation. In this second point, by proposing another epistemological and ontological perspective, these intellectuals expanded the meaning of democracy. In this interpretation, the collective becomes an intrinsic value to democratic thinking and social movements become primary actors in the construction and maintenance of a substantially egalitarian society. Here, culture and aesthetics, in addition to socioeconomic issues, are seen as important political tools, therefore, becoming necessary when dealing with civil rights. In their methodologies, these intellectuals go beyond national borders, bringing a diasporic perspective to the analysis. Thus, they provide us with another sociological interpretation of Brazil, having as one of the central elements the criticism of the racialization process and the inequalities resulting from it. Thus, in general, they defend the proposition of a democracy that does not face difference in a hierarchical way.
Black public intellectuals and the process of democratization of brazilian politics (1985-2012)
Keywords: Democracia; Intelectuais negros; Movimento negro; Políticas públicas; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS